1981
DOI: 10.1111/j.1399-0004.1981.tb00692.x
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial deletion of the long arm of chromosome no. 5 in two unrelated children with congenital anomalies and mental retardation

Abstract: Two unrelated children with partial deletion of the long arm of a chromosome no. 5 are reported. The boy presented with severe hypotonia, developmental delay, and a few minor defects of the face including frontal bossing, antimongoloid slant of the palpebral fissures, depressed nasal bridge and bilateral epicanthal folds. With age, his hypotonia has improved. The parents have normal chromosomes; the mother has a 9qh+ variant. The second patient, a girl, presented at birth with multiple congenital anomalies inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1

Year Published

1982
1982
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 11 publications
1
15
1
Order By: Relevance
“…4). Pescia et al (1978), Stoll et al (1980;q13 -+q15), male patient of Silengo et al (1981 ;q13 +q15), and our case. The malformation syndrome is not severe although very deep hypotonia and myasthenia, abnormal asymmetric skull with brachycephaly and microcephaly, frontal bossing, slight dysmorphic face with flat nose, broad nasal bridge, low-set and malformed ears, narrow palpebral fissures, hypertelorism, strabismus, epicanthus, micrognathia, valgus, flat feet, abnormal dermatoglyphics (frequent whorls on the fingertips, t" triradii, single crease on the 5th finger, simian creases) and severe to moderate mental retardation were observed.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…4). Pescia et al (1978), Stoll et al (1980;q13 -+q15), male patient of Silengo et al (1981 ;q13 +q15), and our case. The malformation syndrome is not severe although very deep hypotonia and myasthenia, abnormal asymmetric skull with brachycephaly and microcephaly, frontal bossing, slight dysmorphic face with flat nose, broad nasal bridge, low-set and malformed ears, narrow palpebral fissures, hypertelorism, strabismus, epicanthus, micrognathia, valgus, flat feet, abnormal dermatoglyphics (frequent whorls on the fingertips, t" triradii, single crease on the 5th finger, simian creases) and severe to moderate mental retardation were observed.…”
Section: Discussionsupporting
confidence: 68%
“…Monosorny of bands q23,q31 was an additional finding in the case of Felding & Kristoffersson (1980) and very probable in the female patient of Centerwall et al (1978) and Silengo et al (1981), with an interstitial deletion q154q31. It appears to induce, in addition, cleft palate and renal (hydronephrosis), eye and cardiac anomalies (persistent ductus arteriosus, ventricular hypertrophy, coarctation of the aorta, and atrial septa1 defect).…”
Section: Cardiac Malformations Psychomotor R E T a R O A I I O N Muscmentioning
confidence: 81%
See 2 more Smart Citations
“…One was identified by autoradiographic studies as a chromosome 5 deletion (Lindenbaum & Butler 1971) and six were identified by G-banding techniques. These six cases present a de novo interstitial deletion with the breakpoints located in region 5q13-5q31 (Erdtmann et al 1975, Pescia et al 1978, Silengo et al 1981, Harprecht-Beato et al 1983).…”
mentioning
confidence: 99%